Impact of antiretroviral treatment on height evolution of HIV infected children - Traisathit, Patrinee (BMC Pediatr, 2019)
BACKGROUND: Antiretroviral treatment (ART) has been shown to have a beneficial effect on the weight evolution but its effect on height remains unclear. We described patterns of height evolution and identified predictors of catch-up growth in HIV-infected children on ART. METHODS: To describe the height evolution from birth to adulthood, we developed a nonlinear mixed effect model using data from perinatally HIV-infected children who initiated ART from 1999 to 2013 in a prospective cohort study in Thailand. The main covariates of interest were: sex, ART regimen (dual nucleoside reverse-transcriptase inhibitor, non-nucleoside reverse transcriptase inhibitor (NNRTI)-, or protease inhibitor (PI)-based), baseline CD4 percentage, HIV-RNA load and CDC HIV Classification stage and occurrence of AIDS-defining events. RESULTS: A total 477 children (43% boys) contributed 18,596 height measurements over a median duration of 6.3 years on ART (interquartile range, 3.0 to 8.3). At ART initiation, median age was 6.2 years (1.8 to 9.6), 16% of children were underweight (weight-for-age z-score < − 2), 49% presented stunting (height-for-age z-score < − 2), and 7% wasting (weight-for-height z-score < − 2). The most frequent regimen at ART initiation was NNRTI-based (79%). A model with 4 components, birth length and 3 exponential functions of age accounting for the 3 growth phases was developed and show that the height-growth velocity was inversely associated with the age at ART initiation, the adult height was significantly lower in those who had experienced at least one AIDS-defining event while, as expected, the model found that adult height in females was lower than in males. Age at ART initiation, type of ART regimen, CDC stage, CD4 percentages, and HIV-RNA load were not associated with the final height. CONCLUSIONS: The younger the children at ART initiation, the greater the effect on height-growth velocity, supporting the World Health Organization’s recommendation to start ART as early as possible. However, final adult height was not linked to the age at ART initiation. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12887-019-1663-8) contains supplementary material, which is available to authorized users.